Dry-land vs. resisted and assisted sprint exercises on swimming sprint performances - Girold, S.; Maurin, D.; Dugue, B.; Millet, G. (First international symposium sciences and practices in swimming, 2006)
Twenty-one competition-level swimmers were randomly divided into three groups: Strength (S), Resisted-and Assisted-Sprint (RAS) and Control (C). During 12 weeks, all swimmers trained six days per week, with two strength dry-land or two RAS sessions for S and RAS, respectively. Barbells were used in Strength training and elastic tubes were used to generate over-strength and over-speed in RAS training. Prior, during (6* week) and after the training period, strength of the elbow flexors and extensors was measured with an isokinetic dynamometer and speed, stroke rate, stroke length and stroke depth recorded using an underwater video System during a 50 m sprint event. After the training period, swimming velocity, elbow flexors and extensors strength increased (p<0.05) while stroke depth decreased in S and RAS (p<0.05). In addition, stroke rate increased in RAS (p<0.05). However, Overall, only slight differences between S and RAS methods were observed despite the greater specificity of RAS in swimmers. No increase in swimming velocity was observed in C.